ANALISIS POLA WAKTU KERJA PRODUKTIF PERAWAT DI UNIT RAWAT INAP RSUD PROF. DR. ALOEI SABOE KOTA GORONTALO - Dea Rahmatia Yunus; Dwi Lassmy Samaritan; Meyrin Kadir (LPPM Universitas Bina Mandiri Gorontalo, 2023)
This research was conducted in the inpatient unitRSUD Prof. Dr. Aloei Saboe Gorontalo City.This type of research is a quantitative research with a survey method. Researchers collect facts and information through questions to respondents who represent the relevant populationproductive working time of nurses in the inpatient unit of Prof. Hospital. Dr. Aloei Saboe. The method used in the research is bymake observations/observations by distributing questionnaires containing questions related to the use of time in carrying out work activities which will be distributed to nursesin the inpatient unit of Prof. Dr. Aloei Saboe as many as 40 respondents. The research results showthatActivities in the inpatient unit of Prof. Dr. Aloei Saboe consists of direct nursing and indirect nursing and nurses in the inpatient unit of Prof. Hospital. Dr. Aloei Saboe works productively during official hours with a proportion of productive time patterns of 373 minutes or the equivalent (6 hours 10 minutes) with a percentage of 85% of 100% of the total working time